Capital Expenditure dan Leverage terhadap Kinerja Keuangan - Muhammad Andhika Mahendra; Endah Susilowati (Journal of Management and Bussines (JOMB), 2022)
This study aims to analyze the effect of capital expenditure and leverage on financial performance. This study applies quantitative research methods and multiple linear regression analysis as the data analysis technique. This study has 84 research samples with research objects in the oil and gas and mineral and coal sub-sector companies listed on the IDX in 2018-2020. The results of the study show that capital expenditure and leverage factors can significantly influence the financial performance of oil and gas and mineral and coal sub-sector companies listed on the IDX in 2018-2020. In conclusion, capital expenditure contributes to financial performance by becoming a fixed asset investment decision that is able to drive the company's operations so that the management of the company's assets is improved. Leverage also contributes to financial performance by being a source of funding to increase and meet the investment, asset and operational needs of the company. Keywords: Capital Expenditure, Financial Performance, Leverage, Profitability